The story of female sex workers in the shadow of sex work coercion: A qualitative study - Zahra Boroumandfar; Reza Esmaeili; Negar Mohaghegh (Wolters Kluwer Medknow Publications, 2022)
Background: What has been less considered in the literature of the sex work research, especially in Iran, is to look at the causes of sex work from the perspective of women. The present study sought to understand the causes of the problem and the experience of female sex workers. Methods: The present study was conducted by using qualitative method. Twenty-eight sex workers participated in the study voluntarily and with informed consent. The researcher conducted deep semistructured interviews. Purposive sampling continued until data saturation was reached. Conventional content analysis of the transcribed interviews and field notes were performed to identify key themes, first by each of researchers separately and then in joint discussions. Results: The main theme of the study, according to the participants, was the sense of "what pushed me into sex worker" which included the five main categories of "despair, psychic restlessness, getting drunk by alcohol and drug, incomplete families, not to be left behind by the sudden social changes." Conclusions: Social and health consequences, especially reproductive health of female sex, workers are affected by several factors. However, to deal with this social and health problems, specific attention should be paid to social factors affecting health. Accordingly, each of the influential variables known in this study could be a target for the country's intervention programs, especially in public health centers and even charities related to the healthcare counseling of sex workers.